Performance Efficiency of Heat Recovery Steam Generator (HRSG) Unit 822-B-202 at TPPI Refinery - Syahrir, Irwan; Puja Ningrat Wibowo; Jamaaluddin Jamaaluddin (Fakultas Teknik UMRI, 2024)
The steam generator is vital equipment in oil and gas refinery industry. One of the steam generator equipment in TPPI Refinery other than boiler is Heat Recovery Steam Generator (HRSG). Determine efficiency performance HRSG Unit 822-B202 in this research using compare between energy heat flow for produce steam and energy heat flow from exhaust gas on HRSG stack. The analyze result of efficiency HRSG Unit 822- B-202 when Start-up Commissioning was gotten 96.42%, on September 2021 92.47%, on October 2021 91.46% and November 2021 88.41%. Has occurred decrease of efficiency from start-up Commissioning until November 2021 about 16.95%. Over the past 3 months, efficiency has tended to decrease since commissioning. The calculated decrease in efficiency after commissioning in September was 3.96%. Then from September to October it decreased by 4.97%. However, in November it decreased again by 8.02%. So the accumulated decrease in efficiency of HRSG 822-B-202 during the quarter from Commissioning to November 2021 is 16.95%. So the average decrease in efficiency per month is 5.65%.